The jungle book [videorecording (DVD)] - Murray, Bill, 1950 September 21-; Kingsley, Ben, 1943-; Elba, Idris; Nyong'o, Lupita; Johansson, Scarlett, 1984-; Kipling, Rudyard, 1865-1936 (Walt Disney Studios Home Entertainment, 2016)
An epic adventure about Mowgli, a man-cub who's been raised by a family of wolves. Mowgli finds he is no longer welcome in the jungle when fearsome tiger Shere Khan, who bears the scars of Man, promises to eliminate what he sees as a threat. Urged to abandon the only home he's ever known, Mowgli embarks on a captivating journey of self discovery, guided by panther turned stern mentor Bagheera, and the free spirited bear Baloo.